C-reactive protein, complement C3 and complement C4 as biomarkers in schizophrenia - Abdull Jalil, Mohd Asyraf; Abd Rahim, Nour El Huda; Mohd Noor, Hanisah; Ku Zaifah, Norsidah; A. Talib, Norlelawati (2021)
Schizophrenia is a chronic mental illness with no specific biomarker. Diagnosis and treatment monitoring mostly depend on clinical symptomatology. A number of immune related proteins have been found to be linked with schizophrenia, but the magnitude of associations are modest at best. This might be due to heterogenous nature of schizophrenia, with certain phenotypes possibly having stronger association. Here we used immunoturbidimetry to measure the plasma levels of complement C3 (C3), complement C4 (C4), and C-reactive protein (CRP) between 183 schizophrenia patients and 212 healthy controls. Patients were assessed using Positive and Negative Symptom Scale (PANSS) to identify clinical phenotypes. We found that both C3 and C4 are significantly, but only modestly higher in patients than in controls. Patients were also more than twice as likely to have elevated CRP levels (relative risk 2.758, 95% C.I. [1.724 - 4.412]. However, no particular clinical phenotype was associated with the levels of C3 or C4, or having elevated CRP. These results suggest that despite showing significant association with schizophrenia, the use of C3, C4 and CRP as biomarker requires further validation. Nonetheless, these results highlight possible role of inflammation or aberrant immune function in the pathophysiology of schizophrenia.